Respostas

2013-11-30T15:13:58-02:00
√(x²+9)- 15/√(x²+9) =2¹
                 √(x²+9) = 2 + 15/√(x²+9)
                 √(x²+9) = (2*(√(x²+9)) + 15)/√(x²+9)   
     √(x²+9)*√(x²+9) = 2*(√(x²+9)) + 15
                   (x²+9) = 2*(√(x²+9)) + 15
                 x²+9-15 = 2*(√(x²+9))  
                Elevando os dois lados da equação ao quadrado
                   x^4 - 12x^2 + 36 = 4*(x²+9)
                   x^4 - 12x^2 + 36 = 4x^2 + 36
                   x^4 - 12x^2 -4x^2 = 0
                 Dividindo tudo por x^2
                                x^2 - 16 = 0
                                       x^2 = 16
                                    x = 4 ou x=-4
 Conjunto solução{ -4; 4}